Intentions to Sustainably Use Air Transportation During the Pandemic: A Structural Equation Model Analysis - Kamilia, Rifka Alifa; Iskandar, Yelita Anggiane; Zulvia, Ferani Eva (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research was motivated by the pandemic due to the Corona-19 virus which resulted in the crippling of the aviation industry. Angkasa Pura II, specifically Soekarno-Hatta Airport, a company specializing in airport services and airport-related services, has experienced a significant decline in its revenue. Specifically, the company has lost an alarming 50% of its total revenue. This substantial decrease in earnings has undoubtedly had a profound impact on the organization's financial stability and future prospects. Soekarno Hatta Airport experienced a decrease in the number of passengers from 27,163,886 people per year in 2019 to a very significant decline in 2020 to 10,139,718. The pandemic has changed people's behavior in traveling using air transportation. One of their considerations is getting infected while traveling. This study aims to examine the effect of passenger satisfaction variables, subjective norms, attitudes, perceptions of behavioral control, and perceptions of travel risk on travel intentions using air transportation during the pandemic. This research was conducted by surveying 145 respondents who had used the services of Angkasa Pura II. The analytical method used in this study is the SEM-PLS with SmartPLS 3.0. Results showed that air travel intentions during the pandemic are significantly affected by passengers' satisfaction, subjective norms, and perceptions of behavioral control. Meanwhile, the variables of attitude and perception of travel risk did not significantly affect the intention to travel using air transportation during the pandemic.